2016
DOI: 10.1002/2059-7932.12009
|View full text |Cite
|
Sign up to set email alerts
|

Is journalism a transnational field? Asymmetrical relations and symbolic domination in online news

Abstract: Are all transnational exchanges ‘fielded’? This article explores the limits of the concept of transnational field by focusing on the case of journalism. At first glance, journalism might seem to be the perfect example of a transnational field. The frequency, speed and extent of international exchanges between media outlets has increased dramatically with the development of online news, leading media scholars to develop the concept of ‘global news’. Yet I argue that such international exchanges do not necessari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…These findings have implications for broader arguments about the extent to which transnational news is “fielded.” Our research supports the findings of others who have pointed to the ongoing dominance of domestic perspectives and personnel (Christin 2016; Denĉik 2012, 2013; Van Leuven and Berglez 2016). The doxic practices of transnational news journalists also involved the news value of negativity, which shapes the production of foreign news in domestic media (Galtung and Ruge 1965).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These findings have implications for broader arguments about the extent to which transnational news is “fielded.” Our research supports the findings of others who have pointed to the ongoing dominance of domestic perspectives and personnel (Christin 2016; Denĉik 2012, 2013; Van Leuven and Berglez 2016). The doxic practices of transnational news journalists also involved the news value of negativity, which shapes the production of foreign news in domestic media (Galtung and Ruge 1965).…”
Section: Resultssupporting
confidence: 92%
“…Yet, analyses of CNN’s output have shown that it tends to be uncritically supportive of U.S. foreign policy (Thussu 2000). Other forms of commercially funded transnational journalism practiced in Belgium, France, and the United Kingdom have also been found to be powerfully shaped by the staff, cultural perspectives, and political interests of news organizations’ states of origin (Christin 2016; Denĉik 2012, 2013; Van Leuven and Berglez 2016).…”
Section: Western Transnational Newsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not just a matter of practices in international organizations producing policy outcomes that implicate hegemonic order. For instance, to the extent that there exists a transnational field of journalism (Christin, 2016: 214), it often becomes a site of power-political struggle in which private journalists, state-sponsored journalists, and direct agents of the state operate. The apparent “weaponization” of Wikileaks by Russian intelligence — in an effort to, at minimum, undermine the legitimacy of the US political system and, at maximum, facilitate the election of Donald Trump — illustrates how struggles within a particular field may combine with the politics of hegemony in ways that elude conventional hegemonic-order theories (see Shane et al, 2017).…”
Section: Hegemonic-order Theory Recastmentioning
confidence: 99%